2016
DOI: 10.5194/hess-20-843-2016
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate sinks and sources as controls of spatio-temporal water quality dynamics in an agricultural headwater catchment

Abstract: Abstract. Several controls are known to affect water quality of stream networks during flow recession periods, such as solute leaching processes, surface water-groundwater interactions as well as biogeochemical in-stream turnover processes. Throughout the stream network, combinations of specific water and solute export rates and local in-stream conditions overlay the biogeochemical signals from upstream sections. Therefore, upstream sections can be considered functional units which could be distinguished and o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…The temporal resolution of the water quality data presents a source of uncertainty and limits the interpretation of cause and effect to some degree. For individual small catchments with different land use in Baden-Württemberg, Lange and Haensler (2012; forest) and Schuetz, Gascuel-Odoux, Durand, and Weiler (2016;agriculture) found that, on a monthly scale, nitrate concentrations can change quickly during low-flow periods. Such changes were not captured by our dataset due to low temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal resolution of the water quality data presents a source of uncertainty and limits the interpretation of cause and effect to some degree. For individual small catchments with different land use in Baden-Württemberg, Lange and Haensler (2012; forest) and Schuetz, Gascuel-Odoux, Durand, and Weiler (2016;agriculture) found that, on a monthly scale, nitrate concentrations can change quickly during low-flow periods. Such changes were not captured by our dataset due to low temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of applications, the Hudson River basin regional scale model may be used to continuously forecast the overall variability of the water resources Pryet et al, 2015;Saraiva Okello et al, 2015), predicting fate and transport of water quality such as nitrate (Schoonover and Lockaby, 2006;Wang et al, 2012;Bastola and Misra, 2015;Schuetz et al, 2016) and climate change scenarios (Ducharne et al, 2007(Ducharne et al, , 2010Graham et al, 2007;Quintana Seguí et al, 2010;Habets et al, 2013). Moreover, socio-economic analysis may be used to weigh how such improved forecasts can prevent loss of life and minimize the damage to property, with the aid of effective communication and social media.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…HEC-HMS, developed by the US Army Corps of Engineers, is a conceptual semi-distributed hydrological model that has been used extensively in rainfall-runoff modeling and other related hydrological studies (Anderson et al, 2002;Neary et al, 2004;Knebl et al, 2005;Amengual et al, 2009;Chu and Steinman, 2009;Halwatura and Najim, 2013;Meenu et al, 2013;Seyoum et al, 2013;Zhang et al, 2013;Yang and Yang, 2014). The model uses a number of adjustable empirically derived parameters that describe the overall structure of the basin including parameters for runoff, baseflow and river routing (Feldman, 2000).…”
Section: Hec-hms Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrate (NO 3 − ) has high mobility and can be lost from the vadose zone by leaching to groundwater because of its solubility and electronegativity (Chowdary, Rao, & Sarma, 2005). Therefore, NO 3 − is the most common pollutant found in shallow aquifers and can cause a crises in related to the drinking water supply and eutrophication of water bodies in local river systems (Gutiérrez, Biagioni, Alarcón-Herrera, & Rivas-Lucero, 2018;Schuetz, Gascuel-Odoux, Durand, & Weiler, 2016). Due to the high fertilizer application rate in modern intensive agricultural production, groundwater nitrate contamination has become a global problem (Chen, Wu, Hu, & Li, 2010;Liu, Ming, & Ankumah, 2005).…”
Section: Introductionmentioning
confidence: 99%